Study on influence of types and numbers of inner-layer shape on failure mechanism of layered alumina ceramic under three-point bending and bending fatigue load - Pengliang Hou; Yang Chen; Huantao Jing (Materials Research Express)
In this paper, the failure mechanism of Layered Alumina Ceramic (LAC) with different types and numbers of inner-layer shapes was investigated under three-point bending (TPB) and bending fatigue load. Moreover, finite element analysis (FEA) models were established. Results of the experiment and FEA models indicate that specimens with different types and numbers of inner-layer shapes show excellent mechanical behavior. Introducing inner-layer shapes causes crack deflection, improving the bending strength and bending fatigue life of LAC specimens with arched or trapezoidal inner-layer shapes. However, taking the trapezoidal inner-layer shape as an example, if its number is more than or less than 19, the deflection of cracks in the inner layer is hindered, reducing the specimen’s mechanical properties. Furthermore, all LAC specimens show a mixed fracture mode. When a trapezoidal or arched inner-layer shape is adopted, transgranular cracks are significantly increased, improving its mechanical properties. However, the number of transgranular cracks is further reduced by changing the number of trapezoidal inner-layer shapes. Therefore, LAC specimens show poor mechanical behavior. In summary, LAC specimens with 19 arches or trapezoids in the inner layer show excellent mechanical properties. This research offers component design engineers the optimal types and numbers of inner-layer shapes for layered alumina ceramic, thereby enhancing the service life of ceramics.